(untitled) (Journal of NELTA Gandaki, 2025)
Mobile technologies have revolutionized English language education (ELE) and, to some extent, transformed English language learning (ELL) globally. Its integration in Nepali higher education is still underexplored. This study explores how mobile-assisted English language learning (MAELL) is perceived in Nepali university settings. It examines the interplay of the intensity and purpose of use, networked access, and behavioural nudges through the narratives of the teachers and students. The study employed a phenomenological qualitative design. We collected data from two English teachers and eight students purposively selected from two universities using semi-structured interviews and guided reflection of the participants. Thematic analysis of the data under four themes showed the participants’ evolving digital literacy, academic use of mobile tools through collaboration, and reflection, despite challenges induced by low-resourced university settings and insufficient technical knowledge. Findings demonstrate that mobile use becomes a learning enabler or disruptor based on learners’ agency and institutional, pedagogical, and sociocultural contexts. This study contributes to a distinctive understanding of MAELL in Nepali low-resourced university settings. It implies the need for localized frameworks to address equity, engagement, autonomy, and ethical use of mobile in academia. Additionally, it invites policy-level support to enhance it for affordable access to ELL resources. It also emphasizes the importance of exploring learners’ stories, experiences, perceptions, and lived realities in educational institutions. Further, this study enhances the discourse on technology-enhanced language education in the Global South by exploring the MAELL experiences in the Nepali universities.